New Data on the Distribution of Red-Listed Vascular Plant Species in the Murmansk Region - Кравченко, Алексей Васильевич; Кожин, Михаил Николаевич; Боровичев, Евгений Александрович; Костина, Валентина Андреевна; Kravchenko, Alexey; Kozhin, Mikhail; Borovichev, Evgeniy; Kostina, Valentina (Trudy Karelʹskogo nauchnogo t͡s︡entra Rossiĭskoĭ akademii nauk, 2016)
Data are provided on newly found locations of 27 vascular plant species red-listed in the Murmansk Region. New information about 12 species (Alisma juzepczukii Tzvel., Asplenium viride Huds., Carex echinata Murr., Cotoneaster laxiflorus Jacq. ex Lindley, Cystopteris dickieana R. Sim, Dactylorhiza fuchsii (Druce) Soó, Dianthus arenarius L. ssp. borussicus Vierh., Draba alpina L., Draba nivalis Liljebl., Gentianopsis detonsa (Rottb.) Ma, Salix gmelinii Pall., and Woodsia glabella R. Br.) considerably broadens the previous ideas about the pattern of their distribution in the region.